Pengaruh Teknologi Komunikasi terhadap Perubahan Pola Interaksi Sosial Masyarakat - Putu Bangli Suri Artani; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
The rapid development of communication technology in the digital era has had a significant impact on people's interaction patterns. One of the important aspects in this case is its influence on communication behavior, both in social, economic, and political life. The Electronic Information and Transaction Law (UU ITE) which was passed in Indonesia in 2008, acts as a regulation to regulate the use of communication technology, especially in cyberspace, with the aim of protecting the public from misuse of technology such as defamation, fraud, and hate speech. This research aims to analyze how the influence of the ITE Law on changes in community interaction patterns in digital space, both positively and negatively. Research results show that although the ITE Law provides a clear legal framework, there are challenges in its implementation that have the potential to hinder freedom of opinion and change the way people interact online. On the other hand, this regulation also spurs the public to be more careful and responsible in communicating through digital platforms.